2020
DOI: 10.3390/nu12040946
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Infant Gut Microbiota and Allergy. The Role of Bifidobacterium breve and Prebiotic Oligosaccharides in the Activation of Anti-Allergic Mechanisms in Early Life

Abstract: The increase in allergy prevalence observed in recent decades may be a consequence of early intestinal dysbiosis. The intestinal microbiota is formed in the first 1000 days of life, when it is particularly sensitive to various factors, such as the composition of the mother’s microbiota, type of delivery, infant’s diet, number of siblings, contact with animals, and antibiotic therapy. Breastfeeding and vaginal birth favorably affect the formation of an infant’s intestinal microbiota and protect against allergy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 101 publications
(145 reference statements)
3
103
2
2
Order By: Relevance
“…71 Bifidobacterium breve is a species commonly isolated from the intestines of healthy breastfed infants and from human milk and is thought to have a significant impact on the development of immune tolerance. 72 In a longitudinal study of a Canadian child cohort, it was found that infants at risk of asthma showed gut microbial changes during the first 100 days of life. Four bacteria taxa were reduced in high-risk children and this was accompanied by reduced deregulation of enterohepatic metabolites.…”
Section: Microbiomementioning
confidence: 99%
“…71 Bifidobacterium breve is a species commonly isolated from the intestines of healthy breastfed infants and from human milk and is thought to have a significant impact on the development of immune tolerance. 72 In a longitudinal study of a Canadian child cohort, it was found that infants at risk of asthma showed gut microbial changes during the first 100 days of life. Four bacteria taxa were reduced in high-risk children and this was accompanied by reduced deregulation of enterohepatic metabolites.…”
Section: Microbiomementioning
confidence: 99%
“…From our experimental results, the relative abundance of Enterobacter increased in β-CG allergic mice and then decreased after LGG intervention. According to reports, the imbalance of gut microbiota is directly related to allergies [ 30 ]. The microbial composition in the intestinal tract of normal mice is diverse, and the proportion of Enterobacter is low.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of HT-29 cells with B. breve strain Bre10 suppresses LPS and TNF-α-induced IL-8 mRNA and protein expression levels [ 109 ]. The B. breve strain M-16V colonizing the breastfed infant gut is regarded as safety [ 111 ], and exerts anti-inflammatory effects on allergic diseases after a single supplementation [ 111 , 112 ], or in combination with B. infantis M-63 and B longum BB536 [ 113 ], including both prenatal and postnatal periods [ 114 ].The probiotic B. breve strain M-16V and galacto/fructo-oligosaccharide (GOS/FOS) prebiotic mixture supplemented with fortified milk increase the relative abundances of Bifidobacterium spp. [ 115 ].…”
Section: Short-chain Fatty Acids: a Link Between Maternal Vlckd Tmentioning
confidence: 99%